A construção do conhecimento em química – no ensino médio – segundo a abordagem Ciência, Tecnologia e Sociedade (CTS) - Stange, Simone Moraes (Universidade Federal de São Carlos, 2017)
This thesis had as main objective to develop a methodology of teaching, as instrument for the construction of the knowledge in chemistry, in the secondary education, according to the approach Science, Technology and Society (CTS), in the surroundings of the CTS Education, having as perspective the analysis of the news from A Voz do Brasil - online radio program, through the study of the occurrences and applications of organic chemistry, involving 40 students of the 3rd grade of the "Barão de Antonina" Basic Education School in the city of Mafra, Santa Catarina state. The research was qualitative of an interpretative nature on documents of a sonorous and descriptive nature (online radio program), using the Participant Observation method - in a continuous process, centralized in the field journal annotations and written productions of the students. with Cervo and Bervian (2002), qualitative research - observes, records, analyzes and relates facts or phenomena - without, however, manipulating them, trying to find out precisely how often a phenomenon occurs. Thus, the students organized themselves into teams, which were directed to access the sound and descriptive records of the online radio program A Voz do Brasil and, based on the analysis of the news, created categories of content analysis and elaborated conceptual maps. This work demonstrates the students 'perceptions of the students' perceptions of the chemistry discipline in the organic chemistry segments, making it meaningful, allowing the student to be connected to the extraclass realities experienced in the daily life and providing them with participation effective in the teaching-learning process. The participants became active agents, which contributed to the acquisition of concepts and from this, the study went from mere moments watertight to knowledge for life. Thus contributing to the formation of a conscious society, whose form of study has provided the student with progressive, effective and enjoyable knowledge. Therefore, the constant search of the committed educator led to the improvement of teaching practices for the teaching of chemistry, being possible to enhance that the CTS approach in the context of CTS Education, enables contributions to solve the daily challenges that permeate the trajectory of the 21st century.
The construction of knowledge in chemistry - in high school - according to the Science, Technology and Society (STS)
Keywords: Educação em química; Aprendizagem significativa; Educação científica e tecnológica; Ensino médio; Ciência, Tecnologia e Sociedade (CTS); Mapa conceitual; A Voz do Brasil – Programa de rádio online; Education in chemistry; Meaningful learning; Scientific and technological education; High school. Science, Technology and Society (STS); Conceitual map; A Voz do Brasil – Online radio program; CIENCIAS HUMANAS